Analysis Effect of Variation Form and Dimension on Structure Reinforced Concrete Column in Kali Kendeng Bridge - Dewantara, Kandida Rahardian; Apriyatno, Henry; Narendra, Alfa; Taveriyanto, Arie (Semarang State University, 2020)
Abstract. Square columns is a rectangular column which has a single stirrup shape and wide distances in - between. In addition, the round column is a column with a spiral section and has a relatively short distance or a relatively smaller distance in - between. Parameters in column planning include reinforcement requirements, column slenderness, buckling factors, interaction diagrams, and ductility. The study used existing rectangular column data with dimensions of 3.5x3.5 m from Kali Kendeng Bridge in the Semarang-Surakarta Toll Road Construction Project. From the field data, variations in the shape of the columns became rounded columns by calculating the moment of inertia of the two cross sections. Variations in dimensions was performed by calculating reinforcement ratio requirements, aiming to produce an effective column design. The first step is to analyze the bridge loading with earthquake loading SNI for the 2833: 2016 bridge and SNI loading for the bridge 1725: 2016. After that, do the calculation of reinforced concrete column requirements and be checked through the SAP2000 application. Then analyze SAP2000 output, so that the moment and shear forces are obtained in square and round columns. Then with the same material that is 30 MPa quality concrete and 390 MPa quality steel, the results obtained slenderness, bending factor and the radius of inertia between square and round columns are the same. The maximum moment value in a square column is 60704.8718 kN-m and the maximum shear is 2358.14 kN. In addition, the round column obtained a maximum moment of 60685.1944 kN-m and a maximum shear of 2358.65 kN. An overview of the relative ductility aspect of 2.7 kN between square and round columns and the ductility value shows the reduced cross-sectional area the smaller the ductility value. Therefore, it is concluded that a round column is better in terms of holding moment and sliding, than a square shaped column.